PENGARUH MODAL KERJA TERHADAP PROFITABILITAS PADA KOPERASI âXâ BANDUNG - Kostini, Nenden; Dai, Ratna Meisa; Andriani, Evi (AdBispreneur, 2018)
ABSTRACTFinancial services cooperatives are classified as Non-bank Microfinance Institutions (MFIs) and become alternative funding for micro, small and medium enterprises (MSMEs). Non-bank MFIs are believed to play a strategic role in meeting the capital needs of MSMEs. However, the role of non-bank MFIs is still low so that the potential of MSME as a supporter of economic growth canât be realized. Cooperative "X" is a savings and loan cooperative with its own capital comes from the principal savings and compulsory savings of members, donations or grants in the form of long-term debt and short-term from the Center for Credit Cooperatives of West Java and some funds of remaining business results. Loan disbursement by Cooperative "X" continues to increase but not accompanied by an increase in own capital thus increasing the amount of debt and interest costs to be paid. This disrupts the circulation of working capital of "X" Cooperatives because most of the capital is used to cover the cost of loan interest so that remaining business results becomes lessened. This study aims to determine the effect of working capital on profitability in Cooperative "X". The research method used is descriptive-associative with quantitative approach, and simple linear regression analysis. Cash Conversion Cycle is used to measure working capital while profitability is measured by ROA. The result of the research shows that Cooperative "X" Bandung has used its working capital efficiently and profit from the use of all its assets fluctuating every year in relatively small amount, besides it is also known that working capital negatively affect profitability.Â Key words: Working Capital, Profitability, Cooperative, Cash Conversion Cycle, ROAÂ ABSTRAKKoperasi jasa keuangan digolongkan sebagai Lembaga Keuangan Mikro (LKM) Non-bank dan menjadi alternatif pendanaan untuk pelaku usaha mikro, kecil dan menengah (UMKM). LKM Non-bank dipercaya dapat berperan strategis dalam memenuhi kebutuhan modal UMKM. Namun kenyataannya peran LKM Non-bank tersebut masih rendah sehingga potensi UMKM sebagai pendukung pertumbuhan ekonomi belum dapat direalisasikan. Koperasi Â âXâ merupakan koperasi simpan pinjam dengan modal sendiri berasal dari simpanan pokok dan simpanan wajib anggota, donasi atau bantuan dana berupa utang jangka panjang maupun jangka pendek dari Pusat Koperasi Kredit Jawa Barat dan sebagian dana SHU. Penyaluran kredit oleh Koperasi âXâ terus meningkat namun tidak diiringi oleh peningkatan modal sendiri sehingga meningkatkan jumlah utang dan biaya bunga yang harus dibayar. Hal ini mengganggu sirkulasi modal kerja Koperasi âXâ karena sebagian besar modal digunakan untuk menutupi biaya bunga pinjaman sehingga SHU menjadi berkurang. Penelitian ini bertujuan untuk mengetahui pengaruh modal kerja terhadap profitabilitas pada Koperasi âXâ. Metode penelitian yang digunakan adalah deskriptif-asosiatif dengan pendekatan kuantitatif, dan analisis regresi linear sederhana. Cash Conversion Cycle digunakan untuk mengukur modal kerja sedangkan profitabilitas diukur dengan ROA. Hasil penelitian menunjukkan bahwa Koperasi âXâ Bandung telah menggunakan modal kerjanya secara efisien dan memperoleh keuntungan dari penggunan seluruh asetnya secara fluktuatif setiap tahunnya dalam jumlah relatif kecil, selain itu diketahui juga bahwa modal kerja berpengaruh negatif terhadap profitabilitasKata kunci: Modal Kerja, Profitabilitas, Koperasi, Cash Conversion Cycle, ROA